THE DEVELOPMENT OF LEARNING ACHIEVEMENT BY INQUIRY-BASED LEARNING (5E) WITH SCIENTIFIC BOARD GAME FOR GRADE 5 STUDENTS - Jehnum , Thanatruenan; Boonprakran, Kettawa (Journal of MCU Nakhondhat, 2023)
This article has the objective for compare the learning achievements between before and after the learning management using a search for Inquiry-based Learning (5E) with Scientific Board Game and between after learning for Inquiry-based Learning (5E) with Scientific Board Game with 80% criterion. The study population consisted of 19 Grade 5 students at Wat-Inthanin School and the researcher conducted research in the first semester of the academic year 2023. The tools used in the research were a learning management plan of Inquiry-based Learning (5E) with Scientific Board Game, Scientific Board Game and the learning achievement form. The researcher has collected data from one experimental group and this was a double-measurement study. The test was performed before the learning management of Inquiry-based Learning (5E) with Scientific Board Game by the learning arrangement. Then the learning management by the researcher was taught by using the learning management plan with the process of Inquiry-based Learning (5E) with Scientific Board Game and after the learning arrangement, the researcher conducted a post-test by the learning arrangement. Take the test scores before studying and after studying that have been obtained. They were analyzed by statistical methods to compare learning achievement between before learning and after learning and during after school compared to the criteria of 80 percent. The researcher took the test scores before and after the learning management for mean and standard deviation. The results were the learning achievement after being managed, They showed that After the learning management the process of Inquiry-based Learning (5E) with Scientific Board Game, the learning achievement after the learning management of the population had an average score ( = 24.11, S.D. + 2.51) higher than before the learning management ( = 13.58, S.D. + 3.53) and the learning achievement the learning management had score ( = 24.11) was higher than the 80% criterion.